Pengaruh Dimensi Ekonomi, Sosial dan Lingkungan terhadap Perencanaan Pembangunan Kawasan Pesisir yang Berkelanjutan di Kabupaten Malang - Litasari, Yustina Wahyu (Jurnal Ilmiah Administrasi Publik, 2018)
The purpose of this study is to examine the influence of economic, social and environmental dimensions in the sustainable development planning of coastal areas in Malang Regency. This type of research is quantitative with survey methods carried out to planners in coastal planning in Malang Regency. The measurement scale used is ordinal scale with cross sectional survey design. And the results showed that, partially, the social and environmental dimensions had a significant effect on sustainable development planning of coastal area in Malang Regency, while the economic dimension had no significant effect. However, together, these three dimensions have a significant effect on the sustainable development planning of coastal area in Malang Regency.